BAKTI ANAK TERHADAP ORANG TUA CHILD NEGLECT: REKONSEPSI KONTEKSTUAL QS. AL-ISRA [17]:24 PERSPEKTIF MA’NĀ CUM MĀGHZĀ - Tsaqila Rizki; Mulizar Mulizar; Muhammad Nuh Rasyid (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study is motivated by the disparity between the normative Islamic teaching of birrul walidain (filial piety) and the contemporary social reality of child neglect perpetrated by parents. This gap raises a fundamental question regarding how children's devotion to parents should be understood when the basic rights of children are unmet from early childhood. The research aims to reinterpret Q.S. Al-Isra [17]:24 contextually using the Ma’nā cum Maghzā approach to uncover the dynamic significance of this verse in addressing the problem of child neglect. Employing qualitative methodology through library research, this study analyzes linguistic, intratextual, intertextual, and historical contexts of the verse before developing its significance for contemporary issues. The findings indicate that historically, this verse corrected pre-Islamic Arab societal practices that marginalized children and the elderly by affirming the family as a space of love and intergenerational responsibility. In the contemporary context, the verse is relevant in balancing the rights and obligations between parents and children within a framework of mubādalah (reciprocity). For children who suffer from child neglect, the verse allows room for adaptive filial piety, such as maintaining basic respect, praying for parents, and setting healthy relational boundaries to safeguard psychological well-being. Consequently, Q.S. Al-Isra [17]:24 establishes a family ethic rooted in holistic caregiving and reciprocal relationships that are just, humane, and pertinent to modern contexts.